Differential associations of serum globulin and albumin-globulin ratio with depression in cancer and non-cancer populations: a cross-sectional study - Yichen Zan; Chongxin Guo; Yue Yin; Guanglu Dong (Frontiers in Psychiatry)
ObjectiveThe association of globulin and albumin-globulin ratio (AGR) with depression in cancer and non-cancer populations remains understudied. Therefore, this study aims to investigate this association and potential differences, with a focus on cancer-specific pathophysiology.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted from 2005 to 2016. The participants were divided into three tertiles of globulin and AGR to explore more detailed associations. Logistic regression, restricted cubic spline (RCS) curves, and subgroup analyses were conducted to assess the associations. Finally, receiver operating characteristic (ROC) curves were applied to evaluate the predictive performance of globulin and AGR for depression.ResultsAfter adjusting for covariates, higher globulin levels were significantly associated with an increased incidence of depression in cancer patients (OR=2.53, 95% CI: 1.69-3.80), while a higher AGR was associated with a reduced incidence (OR=0.28, 95% CI: 0.14-0.58). In the non-cancer group, a similar but weaker association was observed: higher globulin levels (OR=1.16, 95% CI: 1.00-1.35) and lower AGR (OR=0.80, 95% CI: 0.62-1.05) were associated with depression. Subgroup analyses suggested that the associations were more stable in cancer populations, while in non-cancer populations, these associations might be influenced by drinking. AUC values indicated that the biomarkers demonstrated good predictive performance.ConclusionThis study identifies globulin and AGR as novel, cost-effective biomarkers that integrate inflammation and nutrition, providing a convenient and robust means to predict depression, particularly in cancer patients. These findings also offer new perspectives for future dual clinical interventions targeting inflammation and nutrition, as well as experimental research on depression.